Effect of Celery (Apium graveolens L) Addition on Organoleptic Properties of Mocaf Flour-based Wonton Stuffing. - Rofendi, Hawa Auliya; Chusnah, Miftachul; Hartanti, Dyah Ayu Sri (AGARICUS: Advances Agriculture Science & Farming, 2025)
The use of wheat flour continues to dominate the Indonesian food industry despite growing dependency on imports. To reduce this reliance, mocaf (Modified Cassava Flour) offers a promising local alternative with similar characteristics to wheat flour. This study investigates the effect of adding celery (Apium graveolens L.) to the organoleptic properties of mocaf-based wonton filling, including aspects of color, aroma, taste, and texture. The research used a Completely Randomized Design (CRD) with three treatments: P (2 g celery), Q (4 g celery), and R (6 g celery) per 500 g dough. A descriptive qualitative method and ANOVA followed by LSD (Least Significant Difference) test were used for data analysis. Results showed that treatment R (6 g celery) yielded the most favorable sensory outcomes with color 4.60, aroma 5.12, taste 4.89, and texture 4.65. The addition of 6 g celery provided a distinctive green color, strong aroma, pleasant taste, and soft texture without mushiness, significantly improving the organoleptic properties (p<0.05).